The formation of Candomblé : Vodun history and ritual in Brazil - Parés, Luis Nicolau (Latin America in translation/en traducción/em tradução., 2013)
Interweaving three centuries of transatlantic religious and social history with historical and twenty-first century ethnography, the author traces the formation of Candomblé, one of the most influential African-derived religious forms in the African diaspora, with practitioners today centered in Brazil but also living in Europe and elsewhere in the Americas. Originally published in Brazil and not available in English, this translated edition reveals cultural changes that have occurred in religious practices within Africa, as well as those caused by the displacement of enslaved Africans in the Americas.